2014
DOI: 10.11152/mu.2014.2066.161.st1gt2
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sonographic appearances of the yolk sac: which can be associated with adverse perinatal outcome?

Abstract: Aims: The present study aimed to determine whether yolk sacs with abnormal sonographic appearance are associated with adverse perinatal outcomes in both early and late gestation. Matherial and methods: A total of 305 viable singleton pregnancies with gestational age of 6 to 9 weeks were prospectively evaluated with respect to perinatal outcomes and sonographic characteristics of the yolk sacs. Results: An abnormal yolk sac was found in 66 pregnancies. In pregnancies with enlarged yolk sacs a miscarriage occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 13 publications
4
18
2
1
Order By: Relevance
“…19 Tan et al found that large YS correlated well with later risk of miscarriage, while irregular or echogenic YS appearance were unrelated to any increased risk of spontaneous miscarriage. 20 This agrees with the current results showing low rates of abnormal YS shape and echogenicity among cases with established missed miscarriage. The results of Cho et al also agreed with those of the current study that in cases of missed miscarriage with blighted ovum, the commonest YS abnormalities seen were absent or relatively large YS.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…19 Tan et al found that large YS correlated well with later risk of miscarriage, while irregular or echogenic YS appearance were unrelated to any increased risk of spontaneous miscarriage. 20 This agrees with the current results showing low rates of abnormal YS shape and echogenicity among cases with established missed miscarriage. The results of Cho et al also agreed with those of the current study that in cases of missed miscarriage with blighted ovum, the commonest YS abnormalities seen were absent or relatively large YS.…”
Section: Discussionsupporting
confidence: 94%
“…The most recurring associations were absent YS with GD1, normal-sized or small YS with normal-looking embryos, and cystic YS with isolated embryonic malformations. Future research may look into combining our findings with those of previous studies 19,20 for predicting the pregnancy outcome when such anomalies are seen during the first trimester. It may also include assessment of the final outcome of ongoing pregnancies following the detection of abnormal YS diameter, shape, or echogenicity.…”
supporting
confidence: 50%
“…Tan S et al in their study suggested that irregular yolk sac is not associated with increased risk of spontaneous abortion. 17 There was a gender variance seen in the present study related to the gender of the babies. Majority of the live borns having a small yolk sac were female.…”
Section: Discussionmentioning
confidence: 45%
“…Due to this high incidence, multiple studies have been performed investigating various markers which could possibly identify pregnancies destined to be lost. An enlarged YS, greater than 6 mm, has been associated with this devastating pregnancy outcome, while a misshapen YS has minimal prognostic value . However, the YS has always been evaluated cross‐sectionally with only one ultrasound per patient .…”
Section: Introductionmentioning
confidence: 99%